The Implementation of Extensive Reading in Increasing The Reading Comprehension of Eleventh Grade Students at Senior High School - Almiyah Nurbani.L, Mimi; Arid, Muhammad; Munir, Syahrul; Wahyudin, Wahyudin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The purpose of this study was to prove whether the use of extensive reading strategies improves reading comprehension of eighth grade students of SMA Negeri 1 Pagimana. This study applied a pre-experimental design. The population of this study was eleventh grade students of SMA Negeri 1 Pagimana. The sample in this study consisted of 30 students. Data were collected through multiple choice and comprehension questions, to collect data the researcher gave a pre-test and post-test to compare students' achievement in reading comprehension before and after the extensive reading strategy treatment was carried out in the reading process. The researcher used the SPSS 27 program to analyze the data to determine whether there was an effect on students' reading comprehension after the extensive reading strategy was implemented in the learning process, which finally found the value of Z = -2.534 and Asymp.Sig (2-tailed) = 0.011. And because, the value of Asymp.Sig (2-tailed) <0.05 then, it can be concluded that the hypothesis is accepted. That means that the reading comprehension of eleventh grade students of SMA Negeri 1 Pagimana can be improved by using extensive reading strategies.